Intersecting public health and public space: an analysis of two fitness parks in Louisville, Kentucky - Winslow, Jane Futrell (Kansas State University, 2010)
Complex issues and exciting opportunities lie at the intersection of public health and park design. One component of the recently emerging field of design for active living explores the relationship between design and physical activity as part of a transdisciplinary area of study. This study provides the opportunity to view the design strategies that landscape architects have used to design parks through a lens of promoting physical activity. The purpose of this study is to understand design strategies incorporated in two fitness parks in Louisville, Kentucky assist in meeting public health goals for the citizens of Louisville. Two topical areas were explored: the physical design strategies used in the parks; and the collaborative efforts among stakeholders to further the public health agenda for promoting physical activity in the parks. A case study of two community scale fitness parks profiled the characteristics and design philosophies engaged in park development. The methodology, based on qualitative procedures incorporated three types of investigation: 1) collection of background data and documentation of Louisville’s parks and Mayor’s Healthy Hometown Movement; 2) interviews with key stakeholders from public agencies, private non-profit foundations, and selected consultants who have completed parks design work in Louisville; and 3) a case study analysis of two of the fitness parks in the city, based on the background data and input from subject interviews, and an identification of physical design strategies in each park. Identification of design strategies was based on a conceptual framework developed from the disciplines of public health promotion and landscape architecture, and input from local agency stakeholders. A physical activity design strategy inventory form was developed to aid in analysis. Anticipated results were two-fold: 1. Presentation of information to assist landscape architects in designing parks that intentionally provide engaging opportunities for physical activity; and 2. Contribution to the dialogue between landscape architects and public health professionals, informing collaboration on design projects and community programs. Findings revealed that the two parks studied incorporated several physical design strategies that promote physical activity, reflecting the mature park culture in Louisville, Kentucky, home to one of five designed Olmsted Parks and Parkways systems in the United States. The physical activity design strategy inventory form developed in this study as an audit tool warrants additional study as a potential audit and design tool to engage landscape architects designing for physical activity and informing others of ways that park design can play a role in physical activity.
Keywords: Landscape architecture; Public health; Physical activity; Transdisciplinary study; Design; Urban planning; Health Sciences, Public Health (0573); Landscape Architecture (0390); Recreation (0814)